2019
DOI: 10.1128/jb.00192-19
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the Zur Regulon Components and Metal Resistance in Cupriavidus metallidurans

Abstract: The Zur regulon is central to zinc homeostasis in the zinc-resistant bacterium Cupriavidus metallidurans. It comprises the transcription regulator Zur, the zinc importer ZupT, and three members of the COG0523 family of metal-chaperoning G3Etype GTPases, annotated as CobW1, CobW2, and CobW3. The operon structures of the zur and cobW1 loci were determined. To analyze the interplay between the Zur regulon components and metal resistance, deletion mutants were constructed from the wild-type strain CH34 and various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Even though at least 9 additional transport systems exist that may be able to import zinc ions into the cell, these systems could not completely replace ZupT under "normal" (no added zinc) or zinc starvation conditions (14,15). Interference of the zinc chaperone CobW 3 with some of these other uptake systems is responsible for this effect (62). Adding zinc to DzupT cells with the zupTp::gfp fusion resulted in a downregulation of the reporter activity but not to the level observed for the same fusion in the AE104 parent (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though at least 9 additional transport systems exist that may be able to import zinc ions into the cell, these systems could not completely replace ZupT under "normal" (no added zinc) or zinc starvation conditions (14,15). Interference of the zinc chaperone CobW 3 with some of these other uptake systems is responsible for this effect (62). Adding zinc to DzupT cells with the zupTp::gfp fusion resulted in a downregulation of the reporter activity but not to the level observed for the same fusion in the AE104 parent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S9A). Since deletion of zur results in a constitutively high-level expression of the genes in the Zur regulon (13,62), the increased expression of zupTp::gfp in the DzupT mutant compared to the Dzur mutant indicated the presence of another, currently unknown regulatory circuit for zupT expression in the Dzur mutant. The zupTp::gfp activity in the De4 quadruple efflux mutant, which is not known to have a zinc efflux system, was similar to that of the AE104 parent strain under conditions of zinc deprivation, but zupTp::gfp activity was also elevated in the De4 DzupTp mutant at low zinc concentrations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc is a critical cofactor in a great many enzymes – as much as 9% of the entire proteome in eukaryotes and from 5% to 6% in prokaryotes (Andreini et al , 2009). Yet, its singularity has been virtually overlooked [see however studies such as (Bütof et al , 2019)]. Unexpectedly, it was recently observed that the Aspergillus fumigatus mycotoxin, gliotoxin, had a function specifically involving zinc (Seo et al , 2019), and, because this metabolite could act as a specific zinc chelator, this opens up approaches to investigate in depth the role of zinc.…”
Section: Figmentioning
confidence: 99%
“…The zinc‐resistant betaproteobacterium Cupriavidus metallidurans contains three COG0523 members annotated CobW1, CobW2, CobW3, plus one FolE IA and two FolE IB ‐type proteins. As discussed elsewhere in detail (Bütof et al , ), CobW1 is similar to ZagA and may be the ZagA ortholog in C. metallidurans , CobW2 may serve as zinc‐storage depot that releases zinc upon an unknown signal, and although CobW3 has no GTPase activity, it may nevertheless have a regulatory function (Bütof et al ., ). All three CobWs interact with the metal‐cambialistic FolE IB2 protein in the presence of zinc while GTP is not needed for this interaction (Bütof et al ., ).…”
Section: Introductionmentioning
confidence: 96%
“…As discussed elsewhere in detail (Bütof et al, 2019), CobW1 is similar to ZagA and may be the ZagA ortholog in C. metallidurans, CobW2 may serve as zinc-storage depot that releases zinc upon an unknown signal, and although CobW3 has no GTPase activity, it may nevertheless have a regulatory function (Bütof et al, 2019). All three CobWs interact with the metal-cambialistic FolE IB2 protein in the presence of zinc while GTP is not needed for this interaction (Bütof et al, 2019). In contrast, ZagA of B. subtilis does not bind to the FolE IB ortholog, even in the presence of ZTP (Chandrangsu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%